Proceedings of the International Conference on Educational Sciences and Teacher Profession (ICETeP 2018) 2019
DOI: 10.2991/icetep-18.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Motivation, Engagement and Performance of Employee

Abstract: The purpose of this study was to find out the relationship of motivation, engagement and performance of employees. The study is a survey. Samples were randomly selected as many as 200 employees. The population is whole employees at Office of the Ministry of Religion throughout Bengkulu Province. There are three latent variables, that is motivation, engagement and performance employee. The research instruments were the questionnaires of motivation, engagement and performance employee. Each latent variable was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Employee motivation and involvement have a significant influence on MSME performance ( (Nkansah et al, 2023); ((Bustasar et al, 2019)). Research has shown that motivation, both monetary and non-monetary, is a key factor in organizational performance and there is a significant relationship between motivation and employee performance (Aglina Ulfah & Nilasari, 2023).…”
Section: ) Employee Motivation and Engagementmentioning
confidence: 99%
“…Employee motivation and involvement have a significant influence on MSME performance ( (Nkansah et al, 2023); ((Bustasar et al, 2019)). Research has shown that motivation, both monetary and non-monetary, is a key factor in organizational performance and there is a significant relationship between motivation and employee performance (Aglina Ulfah & Nilasari, 2023).…”
Section: ) Employee Motivation and Engagementmentioning
confidence: 99%